Comparison of laparoscopic tubal-preserving surgical management versus methotrexate therapy for tubal pregnancy: A conventional and network meta-analysis - Junwei Liao; Yong Lin; Yan Long (PLoS ONE, 2025)
Background Tubal pregnancy is one of the common emergencies in obstetrics and gynecology. There are various treatment options for tubal pregnancy. However, there is no consensus on how patients should choose among the treatment options that preserve the fallopian tube. This study aims to investigate the difference in prognosis between different treatment options when the tube is preserved in patients with tubal pregnancy. Methods We conducted a search for studies on tubal pregnancy in the PubMed, EMBASE, Web of Science, and Cochrane Library databases. Ultimately, we obtained 8 studies that met the screening criteria. The Jadad scale and NOS were used to evaluate the quality of the studies, and the evidence quality was evaluated and graded according to GRADE guidelines. Stata 17.0 software was used for data analysis. Result A total of 8 studies involving 677 patients were included. Meta-analysis revealed a significant overall difference in the failure rate between methotrexate treatment and salpingostomy for tubal pregnancy(OR=1.582, 95%CI(1.062, 2.358), p = 0.024). Subgroup analysis demonstrated that a single dose of methotrexate was associated with a higher failure rate compared to salpingostomy(OR = 2.044,95%CI(1.20, 3.47), p = 0.008). In contrast, two or more doses of methotrexate did not show a significant difference in failure rate compared to salpingostomy(OR = 1.130, 95% CI(0.62, 2.07), p = 0.692). However, salpingostomy combined with methotrexate showed a lower failure rate compared to salpingostomy alone(OR = 0.11, 95% CI (0.03–0.48), p = 0.003). Network meta-analysis indicated that the salpingostomy combined with methotrexate had the lowest failure rate, while there was no significant difference in failure rates between salpingostomy and methotrexate alone. Conclusion For hemodynamically stable patients with a desire for future fertility, salpingostomy combined with methotrexate is an excellent option for treating tubal pregnancy. This approach has a lower failure rate compared to either methotrexate or salpingostomy alone and appears to have minimal impact on the patient’s quality of life.